Suomen ulkomaankaupan erikoistuminen: Keiden kanssa kilpailemme? - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2007)
– We analyse the exports of industrialised countries in the 1996-2006 period. First, there is a short discussion of the theory of international trade and its recent theoretical developments. After that we have analysed the long-run development of the structure of Finnish exports, and its structure relative to that of other industrialised countries after 1996. The export structure of Sweden is by far the most similar with that of Finland. We also analysed Finland's share in the total exports of industrialised countries and Finland's share in the total exports in terms of its most important export products. Finland's share in total exports has declined a little, but within the group of "old industrialised countries" its share has remained unchanged. Using the Lafay index, we determine that Finland is strongly specialised in the exports of mobile phones and paper products. Furthermore, Finland is specialised in the exports of high-tech products as determined by the OECD. The share of mobile phones in these exports is 70 per cent, however. Finally, we have studied how the share of value added in the value of production in Finnish manufacturing sectors has changed between the 1970s and 2005. On average the ratio has remained relatively stable, but during the past few years it has declined somewhat. There are significant differences between the manufacturing sectors in this respect.
Keywords: F14; 330; CEO compensation; pay for performance; stock options : firm size; CEO compensation; pay for performance; stock options : firm size